The geochemical composition of the Palu Formation from the Palu-Uluova basin, Elazig, Eastern Anatolia (Turkey): Implication of source area, weathering, and tectonic setting - Akkoca, Dicle Bal; Karatas, Osman (Pergamon-Elsevier Science Ltd, 2019)
In this study geochemistry of clastic rocks from the Palu Formation, Eastern Turkey has been investigated. Samples were collected from two sections within the Palu Formation: the Hacimekke section which is composed of alluvial fan deposits and the Hacisamdere section consisting of basin infill material deposited within a braided river exposing parallel to the Eastern Anatolian Fault Zone. X-ray diffraction patterns show that Hacimekke samples are comprised by calcite, clay, mica, quartz, feldspar, dolomite, and serpentine, and Hacisamdere samples are composed of feldspar, clay, mica, amphibole, pyroxene, calcite, and serpentine. Clay minerals of Hacimekke and Hacisamdere sections are chlorite, smectite, and illite, respectively. In both sections concentrations of Fe2O3 and MgO, CaO, MnO, Cr2O3 are enriched with respect to PAAS. This might indicate that the source rock of studied samples is not felsic continental source rocks, like PAAS. Most major, trace and rare earth elements contents of two section samples are generally similar to their catchment area. La/Sc, Th/Sc, Co/Th and Cr/Th of two sample groups reflect similar values, and show basic, neutral rocks rather than acidic rocks. Chondrite-normalized REE patterns of Hacimekke and Hacisamdere samples are characterized by LREE enrichment, relatively flat HREE pattern and no Eu negative anomaly. Chemical index of alteration indicate that chemical weathering in the source area and recycling processes have been more important for Hacimekice samples. Some samples of Hacimekke plot in arc field and other fall in the collision field. Hacisamdere samples are plotted within the arc field.
Keywords: Geochemistry; Source area; Weathering; Palu formation; Eastern Turkey